Analysis of the Management of Swimming Athlete Achievement Development at Tirta Krisna Swimming Club - Dewi, Komang Ayu Krisna; Utami, Ni Komang Dharmi Yuhdi; Dewi, Ni Putu Artila; Widiantini, Komang Kristina Pransiska (Champions: Education Journal of Sport, Health, and Recreation, 2024)
This study aims to analyze the effectiveness of athlete development management at Tirta Krisna Swimming Club in Jembrana Regency. The research is driven by the crucial role of swimming clubs in nurturing high-achieving young athletes. A descriptive qualitative approach was employed, using direct observation, in-depth interviews, and documentation techniques. Participants included coaches, club administrators, parents, and athletes. The findings indicate that the management system encompasses structured training planning, consistent program implementation, active parental involvement, and performance-based evaluation. A diagram of the results shows 40 active athletes of various age groups and a yearly increase in competition participation. Despite limited facilities, strong leadership from coaches and high athlete motivation serve as key success factors. The study highlights the importance of integrated management involving coaches, athletes, parents, and club administrators in forming an effective athlete development ecosystem.